Assessment of benefits and risks in development of targeted therapies for cancer — The view of regulatory authorities. Issue 5 (16th October 2014) - Pignatti, Francesco; Jonsson, Bertil; Blumenthal, Gideon; Justice, Robert
Abstract : Drug licensing and approval decisions involve the balancing of benefits against the risks (harms) in the presence of uncertainty. Typically, the benefits are estimated from primary efficacy endpoints from confirmatory (phase III) clinical trials although exceptions where promising early data from single‐arm studies have led to accelerated approvals are not uncommon, particularly for cancer drugs. The challenge for regulators is to balance early evidence of efficacy that might support approval versus the need to establish clinical benefit based on conclusive evidence. Targeted agents offer the promise that knowledge about the mechanism of the disease will help identify patients with tumors likely to respond, resulting in higher efficacy and less toxicity, and earlier regulatory decisions based on convincing evidence of clinical benefit. In this paper, we describe methods and examples of benefit‐risk assessment of targeted drugs, recent initiatives from EMA and FDA on improving communication about benefits and risks, and discuss future steps. Highlights: Targeted cancer drugs offer the promise of higher efficacy and less toxicity. We describe regulatory issues in drug development and evaluation of targeted drugs. We describe recent initiatives on improving communication about benefits and risks.